The phenolics, antioxidant activity and in vitro digestion of pomegranate (Punica granatum L.) peels: an investigation of steam explosion pre-treatment - Wang, Qi; Yuan, Tinglan; Zhu, Xiaohuan; Song, Gongshuai; Wang, Danli; Li, Ling; Huang, Mingquan; Gong, Jinyan (Frontiers in Nutrition, 2023)
Pomegranate peels, the main byproduct of pomegranate production, are rich in phenolic compounds that are known for their effective antioxidant properties and have vast application prospects. In this study, steam explosion, an environmentally friendly technique, was applied to pretreat pomegranate peels for phenol extraction. We investigated the effects of explosion pressure, duration, and particle size on the content of total and individual phenolics, and antioxidant activity of pomegranate peels before and after in vitro digestion. The optimal conditions for a steam explosion for pomegranate peels in terms of total phenol content were a pressure of 1.5 MPa, a maintenance time of 90 s, and a particle size of 40 mesh. Under these conditions, pomegranate peel extract presented a higher yield of total phenols, gallic acid, and ellagic acid. However, it also had a lower content of punicalin and punicalagin, compared to the unexploded peels. There was no improvement in the antioxidant activity of pomegranate peels after the steam explosion. Moreover, the content of total phenol, gallic acid, ellagic acid, punicalin, and punicalagin, as well as the antioxidant activity of pomegranate peels, all increased after gastric digestion. Nevertheless, there was a large variation in the pomegranate peel processed by different pressure, duration, and sieve fractions. Overall, this study demonstrated that steam explosion pre-treatment could be an efficient method for improving the release of phenolics, especially gallic acid, and ellagic acid, from pomegranate peels.